Peran Notaris dalam Menjamin Kepastian Hukum Peralihan Hak Atas Tanah dalam Perspektif Hukum Agraria di Indonesia - Yulius Efendi (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
The transfer of land rights is an important legal event that impacts legal certainty and the protection of ownership rights. In this process, notaries play a strategic role by drafting authentic deeds, which serve as the legal foundation for the transfer of land rights. This study aims to analyze the role of notaries in ensuring legal certainty in the transfer of land rights and to identify the responsibilities and challenges faced in practice. The research method used is normative legal research with a legislative and conceptual approach. The findings show that notaries play a crucial role in ensuring the formal and material validity of the land rights transfer agreement through the creation of authentic deeds. However, in practice, there are several challenges, such as discrepancies in land data, bad faith from the parties involved, and weak coordination among related institutions. Therefore, to achieve optimal legal certainty, it is necessary to enhance the professionalism of notaries and strengthen the land administration system. With these measures, it is expected that land rights transfers will proceed more smoothly and provide better legal protection for the public. ty.